Oligometastatic Disease Management: Finding the Sweet Spot - Szturz, Petr; Nevens, Daan; Vermorken, Jan B. (Frontiers in Oncology, 2020)
Hematogenous dissemination represents a common manifestation of squamous cell carcinoma of the head and neck, and the recommended therapeutic options usually consist of systemically administered drugs with palliative intent. However, mounting evidence suggests that patients with few and slowly progressive distant lesions of small size may benefit from various local ablation techniques, which have already been established as standard-of-care modalities for example in colorectal and renal cell carcinomas and in sarcomas. In principle, serving as radical approaches to eradicate cancer, these interventions can be curative. Their impact on local control and overall survival has been shown in numerous retrospective and prospective studies. The term oligometastatic refers to the number of distant lesions which should generally not surpass five in total, ideally in one organ. Currently, surgical resection remains the method of choice supported by the majority of published data. More recently, stereotactic (ablative) body radiotherapy (SABR/SBRT) has emerged as a viable alternative. In cases technically amenable to such local interventions, several other clinical variables need to be taken into account also, including patient-related factors (general health status, patient preferences, socioeconomic background) and disease-related factors (primary tumour site, growth kinetics, synchronous or metachronous metastases). In head and neck cancer, patients presenting with late development of slowly progressive oligometastatic lesions in the lungs secondary to human papillomavirus (HPV) positive oropharyngeal cancer are the ideal candidates for metastasectomy or other local therapies. However, literature data are still limited to say whether there are other subgroups benefiting from this approach. One of the plausible explanations is that post-treatment radiological follow-up is usually not recommended because its impact on survival has not been unequivocal, which is also due to the rarity of oligometastatic manifestations in this disease. At the same time, aggressive treatment of synchronous metastases early in the disease course should be weighed against the risk of futile interventions in a disease with already multimetastatic microscopic dissemination. Therefore, attentive treatment sequencing, meticulous appraisal of cancer extension, refinement of post-treatment surveillance, and understanding of tumour biology and kinetics are crucial in the management of oligometastases.